Sistem Notifikasi Token Listrik Menggunakan Metode Fuzzy Tsukamoto Dengan Sms Gateway Berbasis Arduino - Soni; Miftakhul Jannah; Yulia Fatma (Computer Science and Information Technology, 2023)
Rapidly developing technological advances have encouraged the emergence of various increasingly sophisticated electrical measurement equipment, including the Kilo Watt Hour meter (KWH). The weakness of this KWH meter system is that the warning system is only in the form of indicator lights and buzzer alarms which are often ignored by users and their range is limited. Users who are outside the home also cannot know the condition of electricity at home. So an electricity token notification system is needed to make it easier for users. This tool is designed by utilizing Arduino Uno, SIM 800L, Potentio. SIM 800L is used to send SMS notifications and Potentio to simulate the number of electricity tokens. In this tool Tsukamoto Fuzzy method is applied to determine the output condition based on the input value. The purpose of designing this tool is to improve the KWH meter warning system so that it can reach users outside the home.